2012
DOI: 10.1055/s-0039-1698924
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a prophylaxis paste on surface roughness of different composites, porcelain, enamel and dentin surfaces

Abstract: Objective:To investigate the effect of a prophylaxis paste on surface roughness of different composites, enamel, dentin and porcelain surfaces.Methods:Three different composites (FiltekZ250/Group1, Filtek Supreme XT/Group2, Premise/Group3), enamel/Group4, dentin/Group5 and porcelain/Group6 samples were used in this study. All specimens were prepared flat by SiC discs and polished with a diamond polishing paste. The surface roughness measurements were determined with a profilometer after polishing (initial surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 11 publications
1
35
1
3
Order By: Relevance
“…Prophylactic paste, which is applied for professional tooth cleaning to remove accumulated plaque, has options in terms of abrasion grit size, as fine, medium, and hard, according to relative dentin abrasion (RDA) values . In this study, fine‐grit cleaning paste was preferred to obtain sensitive surfaces in accordance with the manufacturer's instructions .…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic paste, which is applied for professional tooth cleaning to remove accumulated plaque, has options in terms of abrasion grit size, as fine, medium, and hard, according to relative dentin abrasion (RDA) values . In this study, fine‐grit cleaning paste was preferred to obtain sensitive surfaces in accordance with the manufacturer's instructions .…”
Section: Discussionmentioning
confidence: 99%
“…Covey et al [21] reported that the surface roughness of glazed glass ceramic was not affected by the application of PPPs while Yurdaguven et al indicated significant increase in surface roughness of polished glass ceramic [22]. Therefore, the purpose of this study was to evaluate the influence of two different types of PPPs on the surface roughness of two microhybrid and one hybrid IRCs and to compare them with two reference ceramic materials that were prepared with two surface treatments (glazed versus polished).…”
Section: Introductionmentioning
confidence: 99%
“…These findings could be explained by the efficient removal of stains from the outermost enamel layer using a more conservative cleaning procedure leaving minimal damage to enamel's inorganic contents, and this surely reflects on the success of the acid-etching procedure. This explanation is indirectly supported by Yudaguven et al, 7 who reported minimal damage of enamel surfaces after polishing using the prophylaxis paste. Furthermore, Osorio et al 25 reported an increase in the surface energy of enamel surfaces subjected to rubber cup prophylaxis polishing.…”
Section: Discussionmentioning
confidence: 70%
“…The developed roughness may, in turn, result in air pockets, which interfere with the appropriate wetting of enamel surfaces with the liquid adhesive. 7 Bassir et al 30 revealed an adverse effect of micro-abrasion on the bond strength of resin adhesive to either normal or fluorosed enamel surfaces. They referred their results to the alteration in enamel surface structure caused by micro-abrasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation